2016
DOI: 10.1371/journal.pone.0163340
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Ribosomal RNA in the Development of Human Cervical Cancer Is Associated with rDNA Promoter Hypomethylation

Abstract: The ribosomal RNA (rRNA) gene encodes rRNA for protein synthesis. Aberrant expression of the rRNA gene has been generally observed in tumor cells and levels of its promoter methylation as an epigenetic regulator affect rRNA gene transcription. The possible relationship between expression and promoter methylation of rDNA has not been examined in human clinical cervical cancer. Here we investigate rRNA gene expression by quantitative real time PCR, and promoter methylation levels by HpaII/MspI digestion and sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 49 publications
(54 reference statements)
3
31
0
Order By: Relevance
“…Consistently, in other malignancies such as cervical and prostate cancer, increased 45S levels were also described. 35,36 Previously, we found that the pro-proliferative effects of ACA11 overexpression are ROSdependent 8 and the current study demonstrates the role of ROS in ribosome biosynthesis in MM cells. ACA11 overexpression increased pre-47S rRNA levels.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Consistently, in other malignancies such as cervical and prostate cancer, increased 45S levels were also described. 35,36 Previously, we found that the pro-proliferative effects of ACA11 overexpression are ROSdependent 8 and the current study demonstrates the role of ROS in ribosome biosynthesis in MM cells. ACA11 overexpression increased pre-47S rRNA levels.…”
Section: Discussionsupporting
confidence: 58%
“…Our findings are consistent with the expanding appreciation of the role of snoRNAs in normal and malignant hematology. 35,36 Previously, we found that the pro-proliferative effects of ACA11 overexpression are ROSdependent 8 and the current study demonstrates the role of ROS in ribosome biosynthesis in MM cells. 14 The tumor suppressor p53 also has been found to regulate the RNA methylase fibrillarin.…”
Section: Discussionsupporting
confidence: 57%
“…It was proposed that DNA hypermethylation and histone deacetylation contributed to rDNA silencing (Chen & Pikaard, ). Previous studies showed that in human cervical cancer tissues and hepatocellular carcinoma tissues, DNA methylation level was decreased in rRNA gene promoter region and the RNA expression level was increased in human cervical cancer and hepatocellular carcinomas (Ghoshal et al, ; Zhou et al, ). Inconsistent with these previous findings, the present study showed the DNA methylation status of rDNA promoter region was essentially unchanged in OSCC tumor samples as compared with matched normal samples.…”
Section: Discussionmentioning
confidence: 98%
“…DNA methylation modulates rRNA gene transcription in multiple cancer types. Hypomethylation led to the hyperactivation of rRNA gene transcription in human hepatocellular carcinomas (Ghoshal et al, 2004), lung cancer (Lu et al, 2009), and cervical cancer (Zhou et al, 2016), whereas hypermethylation led to the repression of rRNA gene transcription in CD34+ cells derived from patients with myelodysplastic syndromes (Raval et al, 2012).…”
mentioning
confidence: 99%
“…rDNA copy number amplification or deletion is related to tumor genetic context, nucleolus activity, proliferation and protein activity in different cancer types [19][20][21][22]. The expression of rDNA also shows aberrant patterns in prostate cancer, cervical cancer, breast cancer and myelodysplastic syndromes [23][24][25][26]. Overexpression of pre-45S ribosomal RNA promotes colon cancer and is associated with poor survival of colorectal patients [27].…”
mentioning
confidence: 99%